Exploring coupled open innovation for digital servitization in grocery retail: From digital dynamic capabilities perspective - Andrejs Čirjevskis (Journal of Risk and Financial Management, 2022)
Open innovation and digital servitization have been hot topics in existing research. Moreover, the latest research in entrepreneurship and general management justifies that the performance results of specific innovation strategies are usually influenced by dynamic capabilities. However, there is little empirical research on the linkage of open innovation, digital servitization, and micro-foundations of digital dynamic capabilities that affect alliance performance. The emerging literature on open innovation provides partial insight into the micro-foundations of digital dynamic capabilities. Based on it, from a dynamic capability perspective, this paper constructs a conceptual model of research including coupled open innovation of collaborative partners, alliance's formation phases, and dynamic digital capabilities and their micro-foundations which impact alliance performance in grocery retail. The paper aims to provide an overarching view of the digital servitization process of grocery retailers and unpack the micro-foundations of the digital transformation of their business models to sustain advantages. Thus, the paper contributes to the research on open innovation, blockchain technology, artificial intelligence, and dynamic capabilities and provides two theoretical propositions. Then, having employed two illustrative case studies, this paper empirically tests theoretical propositions and justifies the role of coupled open innovation strategies for digital servitization and its micro-foundations.
Keywords: 650; artificial intelligence; blockchain; digital servitization; dynamic capabilities; open innovation